PANCREATIC STEATOSIS IS A NEW THERAPEUTIC PROBLEM IN GASTROENTEROLOGY (Literature Review) - Babajanov Abdumurat Sattarovich; Pulatova Sevara Shamsitdinovna (Galaxy International Interdisciplinary Research Journal, 2022)
Currently, pancreatic steatosis is a common accidental finding during ultrasound examination of the abdominal cavity for other reasons and represents a new problem in gastroenterology and pancreatology. In this review article we have made an attempt to give a general idea of pancreatic steatosis, etiopathogenesis, diagnostic methods, as it is of particular importance due to its close connection with type 2 diabetes mellitus, non-alcoholic fatty liver disease and cardiovascular diseases.